'Co-producing affordability' to the electricity service: a market-oriented response to addressing inequality of access in Rio de Janeiro's favelas. Issue 1 (2nd January 2017) - Pilo', Francesca
Abstract : User involvement in service organisation is seen as a potential means of improving and resolving service delivery issues. The aim of this article is to review a market-oriented project involving electricity customers in the favelas – defined here as an example of 'co-producing affordability' to the service – in order to enhance understanding of the diverse collaborative arrangements in service delivery in the South. By examining the part played by the institutional stakeholders involved in the project and the partial dissatisfaction that arose among users, this article will highlight the limitations of this approach for addressing disparities in access to services.